KONTEKSTUALISASI MAKNA JIHAD (Aplikasi Metode Double Movement Fazlur Rahman) - Kasis Darmawan (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2023)
This paper shows that the meaning of jihad contextually by using Fazlur Rahman's double movement method, gives rise to a more constructive and actual meaning of jihad according to the current context. Jihad tends to be understood textually which creates a rigid understanding of jihad and limits the meaning of jihad to war. Jihad basically has a general meaning as effort and sincerity in devoting all efforts and abilities to achieve goals. Contextualization of jihad in the current Indonesian context can be carried out in the form of economic jihad to tackle the problem of poverty, jihad in the field of education to overcome the problem of educational backwardness, political jihad by upholding a healthy and just democratic system, and jihad of religious moderation amid the growing understanding of radicalism, extremism or terrorism